Nghiên cứu chế tạo, cấu trúc và tính chất của nanocompozit trên cơ sở cao su tự nhiên và silica biến tính silan. Phần I – Sự hình thành nanocompozit - Hưng, Đặng Việt; Chương, Bùi; Minh Ngọc, Phan Thị; Nam, Hoàng (Vietnam Journal of Chemistry, 2014)
Natural rubber/silica nanocomposite were prepared by mixing aqueous suspension of bis(3-triethoxysilylpropyl) tetrasunfit silane (TESPT) modified silica with Hevea Brasilienis latex using a pulverisette type mixer. Dispersion of the modified silica was characterized by laser scattering particle size distribution analyzer and SEM. The results showed that silica in suspension with statistical parameters: median 3.5 (mm); mean 3.8 (mm); variance 4 (mm2); standard deviation 2 (mm) is necessary to make nanocomposite with size distribution in range of 30 - 100 nm.